Colon Drug Targeting: Overview on Dosage Form Designing and Evaluation Aspects - Kantrol Kumar Sahu; Reena Kaushik; Vipul Kumar; Sweety Lanjhiyana; S. K. Lanjhiyana (Colon Drug Targeting: Overview on Dosage Form Designing and Evaluation Aspects, 2022)
Orally administered drug is still most preferred, acceptable, self satisfactory and fulfills patient compliance. Colon has gained much attention in last decades as a potential area of drug exploration both for local and systemic effects. Colon targeted drug delivery system (CDDS) reduces the systemic side effect of drug as well as more effective. Patient compliance is increased by CDDS (as it is painless and self administration is possible) along with the global pharmaceutical market for biologics specially protein and peptides drug. Thus, various approaches have been explored to make drug delivery system more accurate and appropriate. Some of the strategies which are covered in this literature are pressure controlled drug-delivery systems, novel colon targeted delivery system (CODESTM), timed release/delayed release dosage forms, osmotic controlled drug delivery (ORDS-CT), hydrogel systems and beads, bioadhesive systems and nanoparticles respectively. Role of colonic microflora in degradation of polymers and drug release from dosage form have been discussed. This article deals with the novel strategies and their advancements for designing and evaluation strategies of those colon targeted drug delivery system. Pharmaceutical application of these newer techniques and their limitations are covered in this article.